Finding Customer Perception of Peer-to-Peer (P2P) Lending Financial Technology in Pohon Dana - Joshua Tandiono; Brata Wibawa Djojo; Sevenpri Candra; Pantri Heriyati (Binus Business Review, 2020)
The research aimed to discover some factors influencing customer perception toward Peer-to-Peer (P2P) lending Financial Technology (FinTech). It was an empirical study in which the survey was conducted using an online questionnaire from June to August 2019. The research sample was collected from 56 respondents of Pohon Dana customers by simple random sampling. The data collected were analyzed with Partial Least Square Path Modelling by presenting several factors influencing customer perception. The analysis tool was SmartPLS ver 3.2.8. The research finds out that benefits and security have a positive and significant relationship to customer perception. Meanwhile, ease of use, self-efficacy, and trust have a negative and insignificant relationship to customer perception.